Arte Postal na escola: um percurso participativo em conhecimentos artísticos - Toffoli, Edna Márcia Duarte (2020)
This research permeates the reflection on the need for proper methodologies in art teaching. It uses the theme of mail art and aims to collaborate in the teaching and learning process, creating a path of artistic knowledge promoting the participation of students in the mail art network. Based on the experiences of the teacher and postal artist and the possible contributions to art teaching based on the potential of postal art, its history, its origin, in the precursor participating artists, and references in artistic movements such as dadaism, surrealism and conceptual art, as well as in its operating structure. For the understanding of its structure by the students, participation was guided in the creation of a call that enabled the collection of data presenting as a result the analysis of the works received and the exposure of these works as artistic and didactic material, verifying the knowledge acquired with the experience proposed to students. This research was carried out with high school students of the Francisco Cândido Xavier State School, in the city of Uberaba, Minas Gerais. It is characterized by the qualitative methodological approach, forwarded in A/r/tography, with phenomenological method, in a narrative and descriptive way.